The Effectiveness of Islamic Education Management in Strengthening Religious Moderation at State Junior High School 3, Tarakan City - Nurul Farikhatus S (Journal of Education and Teaching Learning, 2026)
This study aims to analyze the implementation of Islamic education management in strengthening religious moderation at SMP Negeri 3 Tarakan City, assess its effectiveness in shaping moderate student character, and identify factors that support and hinder its implementation. The study used a qualitative approach with a case study method through observation, in-depth interviews, and documentation. The results indicate that strengthening religious moderation has been systematically implemented through educational management functions, including planning, organizing, implementing, and monitoring. The values ​​of religious moderation are integrated into learning, religious activities, and school culture, emphasizing tolerance, respect for diversity, and strengthening national character. The implementation of Islamic education management has proven effective in developing tolerant, inclusive, non-violent students with a strong national commitment. Inhibiting factors include the influence of poorly controlled digital media, differences in students' religious understanding, limited mentoring programs, and social environmental challenges. This study confirms that Islamic education management plays a strategic role in strengthening religious moderation and building a harmonious, inclusive, and character-oriented educational culture for students